FLEXIBILITY PROGRAMS AND EXERCISES WITHIN PHYSICAL EDUCATION CLASSES, IN SCHOOLCHILDREN, AND THEIR EFFECT ON THE IMPROVEMENT OF HAMSTRING EXTENSIBILITY: A SYSTEMATIC REVIEW - Soriano-Férriz, Beatriz (2018)
The objective of the present scientific article was to consider the existing scientific literature on the effects that the programs and stretching exercises that are part of the Physical Education classes on the extensibility of the hamstring musculature produce in primary school children. We searched 5 electronic databases in the period from 2007-2017. 22 articles were found, only 12 were analyzed fulfilling the inclusion criteria. From the manual search of the bibliographic references, 3 more were added, with a total of 15 articles included. The results indicated that it is possible to develop hamstring extensibility in school children through programs and stretching exercises in Physical Education classes. The scores on the tests improve significantly in the experimental groups, but not in the control groups. The programs and the exercises can be carried out in the warm-up phase and in the return to calm, being more effective in this second phase. A stretch volume between 4-7 minutes and 2-4 classes per week, obtain statistically significant improvements in levels of extensibility. Up to 1 minute of volume causes increase. After 5 weeks of detraining the levels decrease. Physical Education professionals should include programs and stretching exercises in their classes to provoke an improvement in hamstring extensibility in school children. The increase in the range of movement is related to the effectiveness of sports practice, the reduction of low back pain and alterations in the rachis and the prevention of injuries.